A high-strength mixed rubber and its preparation process

By using modified nanofillers and modified resins in the mixed rubber, combining surface group connection and crosslinking, the problem of unbalanced performance in the prior art is solved, and high mechanical strength, waterproof, aging resistance and resistance are achieved The improvement of acid and alkali performance has expanded the application range of rubber.

CN118638422BActive Publication Date: 2024-12-13QINGHE COUNTY YAOHUA RUBBER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411107487.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-13
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

Existing mixed rubbers are difficult to maintain high mechanical strength while taking into account waterproof, aging resistance and acid-alkali resistance, resulting in reduced application strength and unbalanced performance.

Method used

Modified nanofillers and modified resins are used to enhance the mechanical strength and waterproofing properties of the rubber through surface group connection and cross-linking, and reduce hydrophilicity through the frame structure to form a composite structure to improve acid and alkali resistance.

Benefits of technology

On the basis of maintaining high mechanical strength, the waterproof, aging resistance and acid-base resistance of the mixed rubber are significantly improved, the quality of its comprehensive application is enhanced, and the application field and environment are broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of rubber, and in particular to a high-strength mixed rubber and its preparation process. The high-strength mixed rubber, in terms of mass parts, comprises the following raw materials: 80-120 parts of base rubber, 25-45 parts of modified nanofiller, 20-30 parts of modified resin, 5-10 parts of dispersant, 2-4 parts of structure control agent, 1-2 parts of vulcanizer, 0.5-1.5 parts of accelerator, 1-2 parts of antioxidant, and 4-10 parts of plasticizer. The mixed rubber prepared in the present application can maintain high mechanical strength while ensuring that the mixed rubber itself has excellent waterproof, aging resistance and acid and alkali resistance, while taking into account multiple performance requirements, greatly improving the application quality of the mixed rubber and broadening the application field and environment of the mixed rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of rubber, and in particular to a high-strength mixed rubber and a preparation process thereof. Background Art

[0002] Rubber compounding is a process of mixing raw rubber with various compounding agents to improve its physical properties. Compounding can improve the mechanical strength, aging resistance, wear resistance and other properties of rubber products and make them meet specific application requirements.

[0003] With the progress of the rubber industry, mixing technology has also experienced significant development. Traditional open rubber mixing mills (open mixing mills) and closed rubber mixing mills (internal mixers) are still the mainstream equipment. In recent years, in order to improve efficiency and product quality, continuous mixing technology and computer-controlled mixing systems have emerged. Continuous mixing technology achieves more stable mixing quality through automated processes, while computer control systems can accurately control temperature, pressure and other key parameters, thereby reducing human errors.

[0004] With the further automation of mixing technology, the application of mixing rubber and new material technology will follow. New compounding agents are constantly being developed, such as nano-scale fillers, high-performance antioxidants, etc. These new compounding agents help to improve the comprehensive properties of rubber products, such as enhancing their heat resistance and chemical resistance, and by optimizing the proportion and sequence of compounding agents, the mixing effect can be further improved.

[0005] However, the existing technology also has limitations. For example, in order to give the compound rubber other properties, its mechanical properties are constantly sacrificed, resulting in a significant decrease in the overall application strength. In addition, it is difficult to balance multiple properties for the finished product of the compound rubber. For example, the existing compound rubber cannot effectively take into account the mechanical properties, waterproof properties, aging resistance, etc. of rubber, which greatly limits the overall application of the compound rubber.

[0006] Therefore, in order to solve the above problems, the present application provides a high-strength compound rubber and a preparation process thereof. The compound rubber prepared in the present application can maintain high mechanical strength while ensuring that the compound rubber itself has excellent waterproof, aging resistance and acid and alkali resistance, while taking into account multiple performance requirements, greatly improving the application quality of the compound rubber and broadening the application field and environment of the compound rubber. Summary of the invention

[0007] In order to solve the above problems, the first aspect of the present application provides a high-strength compound rubber, the raw materials of which are, by mass: 80 to 120 parts of base rubber, 25 to 45 parts of modified nanofiller, 20 to 30 parts of modified resin, 5 to 10 parts of dispersant, 2 to 4 parts of structure control agent, 1 to 2 parts of vulcanizer, 0.5 to 1.5 parts of accelerator, 1 to 2 parts of antioxidant, and 4 to 10 parts of plasticizer.

[0008] As a preferred solution, the mass ratio of the base rubber, the modified nanofiller and the dispersant is (9-11): (2.8-4): (0.6-0.8).

[0009] As a preferred solution, the mass ratio of the base rubber, the modified nanofiller and the dispersant is (9.5-10.5): (3-3.6): (0.7-0.8).

[0010] As a preferred solution, the mass ratio of the base rubber, modified resin and plasticizer is (9~11): (2.2~2.8): (0.5~0.8).

[0011] As a preferred solution, the mass ratio of the base rubber, modified resin and plasticizer is (9.5~10.5):(2.4~2.6):(0.6~0.7).

[0012] As a preferred solution, the base rubber is a composition of methyl vinyl silicone rubber and nitrile rubber.

[0013] As a preferred solution, the mass ratio of the methyl vinyl silicone rubber to the nitrile rubber is (3-4): (1.5-2).

[0014] As a preferred solution, the mass ratio of the methyl vinyl silicone rubber to the nitrile rubber is 3.8:1.8.

[0015] As a preferred solution, the vinyl content of the methyl vinyl silicone rubber is 3-4.5%.

[0016] As a preferred solution, the vinyl content of the methyl vinyl silicone rubber is 3.5-4%.

[0017] As a preferred solution, the weight average molecular weight of the methyl vinyl silicone rubber is 500,000 to 700,000.

[0018] As a preferred solution, the weight average molecular weight of the methyl vinyl silicone rubber is 550,000 to 650,000.

[0019] As a preferred scheme, the preparation process of the modified nanofiller includes the following steps: S1: adding silica to deionized water and stirring evenly, adding succinic anhydride and γ-aminopropyltriethoxysilane, heating to 65-70°C, keeping warm and stirring for 2-3 hours to obtain pretreated silica; S2: mixing the pretreated silica and copper acetate, adding them to the DMF solution and stirring evenly, then dropping the DMF solution containing zinc oxide and trimesic acid, the dropping temperature is 50-55°C, the dropping time is 1-1.5 hours, and stirring is continued at a speed of 100-140 r / min; S3: after the dropwise addition is completed, the temperature is raised to 70-75°C, the speed is continuously stirred at 200-240 r / min for 3-4 hours, and the product solution is centrifuged and filtered, and vacuum dried to obtain.

[0020] As a preferred solution, the mass ratio of silicon dioxide, succinic anhydride and γ-aminopropyltriethoxysilane is (2.5-2.8): (1.5-1.6): (0.3-0.35).

[0021] As a preferred solution, the average particle size of the silicon dioxide is 25-30 nm.

[0022] As a preferred solution, the mass ratio of silicon dioxide, zinc oxide, copper acetate and trimesic acid is (2.5-2.8): (0.5-0.8): (3-4): (2-2.5).

[0023] As a preferred solution, the average particle size of the zinc oxide is 10-15 nm.

[0024] By adding the above-mentioned modified nanofiller in the present application, it is possible to improve its waterproof, aging-resistant and acid-alkali-resistant properties while maintaining the excellent mechanical strength of the mixed rubber. First, the modified nanofiller added in the present application can be actively connected with the rubber molecule through the connection of its surface group, and the connection strength of the rubber system is greatly enhanced by the intermolecular force between them, thereby improving the mechanical strength; secondly, it can also effectively help control the network structure of the rubber connection system during the vulcanization process, achieve a more uniform vulcanization effect, and avoid the problem of inconsistent vulcanization; finally, the composite structure formed by the modified nanofiller with nanoparticles as the surface layer attachment and framework particles as the main skeleton can greatly reduce the hydrophilicity of the rubber system through the extremely low surface energy of the framework structure, and can absorb residual trace moisture inside the system, reduce the formation speed of the surface hydration layer, thereby effectively realizing the improvement of waterproofness, mechanical properties, aging resistance and acid-alkali resistance.

[0025] As a preferred solution, the preparation process of the modified resin includes the following steps: S1: adding 2-ethylhexyl acrylate, isobornyl acrylate and benzophenone into a reaction container under nitrogen at a wavelength of 300-380 nm for reaction for 1-2 hours, and filtering the precipitate after the reaction to obtain a prepolymer; S2: mixing the prepolymer with acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether uniformly and adding them to an acetone solvent, then adding benzoyl peroxide, and heating to 70-80° C. and stirring in a closed manner for reaction for 5-7 hours to obtain a preproduct; S3: mixing the preproduct with succinic anhydride and a silane coupling agent in deionized water, maintaining the temperature at 65-70° C. for reaction for 2.5-3 hours, and filtering and washing the product after completion, and vacuum drying it to a water content of ≤1wt%.

[0026] As a preferred embodiment, the mass ratio of 2-ethylhexyl acrylate, isobornyl acrylate, acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether is (4-6): (1-2): (30-35): (3-5): (1.5-2).

[0027] As a preferred embodiment, the mass ratio of 2-ethylhexyl acrylate, isobornyl acrylate, acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether is (5-5.5): (1.4-1.6): (32-35): (3-4): (1.6-1.8).

[0028] As a preferred solution, the mass ratio of the pre-product, succinic anhydride and silane coupling agent is (2.2-2.5): (1.2-1.5): (0.2-0.25).

[0029] As a preferred solution, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0030] The modified resin added in the present application can effectively improve the mechanical properties, waterproofness, aging resistance, acid and alkali resistance and other properties of the mixed rubber system. The added modified resin can produce a good cross-linking effect with the rubber system through the multi-active groups it carries, greatly increasing the compactness of the internal network structure of the rubber system, thereby greatly limiting the migration efficiency of free groups, free water molecules and active molecules in the rubber system after molding, reducing the probability of collision between them, and can accelerate the dispersion and extension of the modified nanofiller in the rubber system, thereby greatly reducing the probability of invasion of external molecules, and then in the long-term use process, increase the resistance of water molecules and active molecules to rubber penetration, thereby obtaining excellent overall performance.

[0031] As a preferred solution, the dispersant is at least one of lauryl alcohol polyoxyethylene ether, cetyl stearyl alcohol polyoxyethylene ether, dodecyl dimethyl betaine, and sodium dodecylbenzene sulfonate.

[0032] As a preferred solution, the dispersant is dodecyl dimethyl betaine.

[0033] As a preferred solution, the structure control agent is at least one of paraffin oil, cyclohexane oil, vegetable oil and polyethylene wax.

[0034] As a preferred solution, the structure control agent is paraffin oil.

[0035] As a preferred solution, the vulcanizing agent is at least one of DTDM, DPTU, DCP and sulfur powder.

[0036] As a preferred solution, the vulcanizing agent is DTDM.

[0037] As a preferred solution, the accelerator is at least one of MBT, MBTS, CBS, TBBS, TMTD, ZBEC, ZDEC, and ZDBC.

[0038] As a preferred solution, the accelerator is a combination of MBT and TMTD.

[0039] As a preferred solution, the mass ratio of MBT to TMTD is (2.5-2.8): (1-1.2).

[0040] As a preferred solution, the antioxidant is at least one of zinc dibutyldithiocarbamate, 2,6-di-tert-butyl-4-methylphenol, and 2-mercaptobenzimidazole.

[0041] As a preferred solution, the antioxidant is zinc dibutyldithiocarbamate.

[0042] As a preferred solution, the plasticizer is at least one of dioctyl phthalate, dinonyl phthalate, triphenyl phosphate, and DOTP.

[0043] As a preferred solution, the plasticizer is a combination of dioctyl phthalate and triphenyl phosphate.

[0044] As a preferred solution, the mass ratio of dioctyl phthalate to triphenyl phosphate is (3-4):(0.5-1).

[0045] The second aspect of the present application provides a preparation process of the above-mentioned high-strength mixed rubber, which specifically includes the following steps: S1: adding the base rubber to a mixer, heating it to 90~100℃, and plasticizing for 10~15min; S2: after plasticizing, adding a mixture of modified nanofiller and dispersant, heating it to 110~120℃, and mixing it for 10~15min; S3: adding a structure control agent and a modified resin, heating it to 140~150℃, and mixing it for 5~10min; S4: continuing to add a vulcanizer, an accelerator, an antioxidant and a plasticizer, and cooling it to 110~120℃, and mixing it for 5~10min; S5: after completion, cooling it to 20~30℃ to obtain a mixed material, then cutting and granulating the mixed material, adding it to a vulcanizer, heating it to 160~180℃, vulcanizing it for 15~25min, taking out the product and molding it.

[0046] The beneficial effects of this application are:

[0047] 1. The high-strength mixed rubber provided in the present application can maintain high mechanical strength while ensuring that the mixed rubber itself has excellent waterproof, aging and acid-base resistance, while taking into account multiple performance requirements, greatly improving the application quality of the mixed rubber and broadening the application field and environment of the mixed rubber.

[0048] 2. A high-strength mixed rubber provided in the present application can improve its waterproof, aging and acid-alkali resistance while maintaining the excellent mechanical strength of the mixed rubber by adding the above-mentioned modified nanofiller; the modified nanofiller added in the present application can actively connect with the rubber molecules through the connecting action of its surface group, and greatly enhance the connection strength of the rubber system through the intermolecular force between them, thereby improving the mechanical strength; and the composite structure formed by the modified nanofiller with nanoparticles as the surface attachment and framework particles as the main skeleton can greatly reduce the hydrophilicity of the rubber system through the extremely low surface energy of the framework structure, and can absorb residual trace moisture inside the system to reduce the formation rate of the surface hydration layer, thereby effectively achieving the improvement of waterproofness, mechanical properties, aging resistance and acid-alkali resistance.

[0049] 3. A high-strength mixed rubber provided in the present application, wherein the modified resin added thereto can effectively improve the mechanical properties, water resistance, aging resistance, acid and alkali resistance and other properties of the mixed rubber system; the added modified resin can produce a good cross-linking effect with the rubber system through the multiple active groups it carries, greatly increasing the compactness of the internal network structure of the rubber system, thereby greatly limiting the migration efficiency of free groups, free water molecules and active molecules in the molded rubber system, reducing the probability of collision between them, and can accelerate the dispersion and extension of the modified nanofiller in the rubber system, thereby greatly reducing the probability of invasion of external molecules, and then in the long-term use process, increasing the resistance of water molecules and active molecules to the penetration of rubber, thereby obtaining excellent overall performance. DETAILED DESCRIPTION

[0050] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0051] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art. Example 1

[0052] Example 1 The first aspect provides a high-strength compound rubber, the raw materials of which are, by mass, 104.5 parts of base rubber, 32.5 parts of modified nanofiller, 25.6 parts of modified resin, 7.8 parts of dispersant, 2.2 parts of structure control agent, 1.4 parts of vulcanizer, 1 part of accelerator, 1.2 parts of antioxidant and 6.2 parts of plasticizer.

[0053] The base rubber is a composition of methyl vinyl silicone rubber and nitrile rubber, and the mass ratio of the two is 3.8:1.8.

[0054] The vinyl content of methyl vinyl silicone rubber is 3.6%, and the weight average molecular weight is 580,000. It was purchased from the corresponding products sold by Hubei Xingyan New Materials Technology Co., Ltd.

[0055] The nitrile rubber was purchased from Jinan Shuangying Chemical Co., Ltd., a liquid nitrile rubber product with a weight average molecular weight of 12,000.

[0056] The preparation process of the modified nanofiller includes the following steps, calculated by mass: S1: adding 2.65 parts of silica to 100 parts of deionized water and stirring evenly, adding 1.55 parts of succinic anhydride and 0.32 parts of γ-aminopropyltriethoxysilane, heating to 65°C, keeping warm and stirring for 3 hours to obtain pretreated silica; S2: mixing the pretreated silica and 3.6 parts of copper acetate, adding them to 100 parts of DMF solution and stirring evenly, then adding a DMF solution containing 0.75 parts of zinc oxide and 2.2 parts of trimesic acid (a total of 65 parts) dropwise, the dropping temperature is 55°C, the dropping time is 1 hour, and stirring is continued at a speed of 120r / min during the period; S3: after the dropwise addition is completed, the temperature is raised to 70°C and the speed is continuously stirred at 220r / min for 3 hours, and the product solution is centrifuged and vacuum dried to obtain the product.

[0057] The average particle size of silicon dioxide is 25 nm; the average particle size of zinc oxide is 12 nm.

[0058] The preparation process of the modified resin includes the following steps, calculated by mass: S1: adding 4.8 parts of 2-ethylhexyl acrylate, 1.6 parts of isobornyl acrylate and 0.1 part of benzophenone into a reaction container, irradiating the reaction for 2 hours at a wavelength of 360 nm under nitrogen, and filtering the precipitate after the reaction to obtain a prepolymer; S2: uniformly mixing the prepolymer with 32.5 parts of acrylamide, 3.8 parts of malonic acid and 2 parts of hydroxymethyl bisphenol A diglycidyl ether, adding the mixture into 200 parts of acetone solvent, then adding 0.14 parts of benzoyl peroxide, heating to 75°C, stirring the mixture in a closed manner for 6.5 hours, and obtaining a preproduct; S3: mixing 2.4 parts of the preproduct with 1.4 parts of succinic anhydride and 0.22 parts of γ-aminopropyltriethoxysilane in 150 parts of deionized water, maintaining the temperature at 65°C for 2.5 hours, filtering and washing the product after completion, and vacuum drying the mixture to a water content of ≤1wt%.

[0059] The dispersant is dodecyl dimethyl betaine; the structure control agent is paraffin oil #3.

[0060] The vulcanizing agent is DTDM; the accelerator is a combination of MBT and TMTD, and the mass ratio of the two is 2.6:1.2.

[0061] The antioxidant is zinc dibutyl dithiocarbamate; the plasticizer is a composition of dioctyl phthalate and triphenyl phosphate, and the mass ratio of the two is 3.5:0.8.

[0062] The second aspect of the present application provides a preparation process of the above-mentioned high-strength compound rubber, which specifically includes the following steps: S1: adding the base rubber to a mixer, heating to 95°C, and plasticizing for 12 minutes; S2: after plasticizing, adding a mixture of modified nanofiller and dispersant, heating to 118°C, and mixing for 11 minutes; S3: adding a structure control agent and a modified resin, heating to 145°C, and mixing for 8 minutes; S4: continuing to add vulcanizer, accelerator, antioxidant and plasticizer, and cooling to 115°C, mixing for 6 minutes; S5: after completion, cooling to 25°C to obtain a compound, then cutting and granulating the compound, adding it to a vulcanizer, heating to 165°C, vulcanizing for 20 minutes, taking out the product and molding it.

[0063] Example 2

[0064] Example 2 The first aspect provides a high-strength compound rubber, the raw materials of which, in parts by mass, are: 98.8 parts of base rubber, 28.6 parts of modified nanofiller, 23.5 parts of modified resin, 6.6 parts of dispersant, 2.2 parts of structure control agent, 1.4 parts of vulcanizer, 1 part of accelerator, 1.2 parts of antioxidant, and 5.5 parts of plasticizer.

[0065] The base rubber is a composition of methyl vinyl silicone rubber and nitrile rubber, and the mass ratio of the two is 4:1.5.

[0066] The vinyl content of methyl vinyl silicone rubber is 3.6%, and the weight average molecular weight is 580,000. It was purchased from the corresponding products sold by Hubei Xingyan New Materials Technology Co., Ltd.

[0067] The nitrile rubber was purchased from Jinan Shuangying Chemical Co., Ltd., a liquid nitrile rubber product with a weight average molecular weight of 12,000.

[0068] The preparation process of the modified nanofiller includes the following steps, calculated by mass: S1: adding 2.65 parts of silica to 100 parts of deionized water and stirring evenly, adding 1.55 parts of succinic anhydride and 0.32 parts of γ-aminopropyltriethoxysilane, heating to 65°C, keeping warm and stirring for 3 hours to obtain pretreated silica; S2: mixing the pretreated silica and 3.6 parts of copper acetate, adding them to 100 parts of DMF solution and stirring evenly, then adding a DMF solution containing 0.75 parts of zinc oxide and 2.2 parts of trimesic acid (a total of 65 parts) dropwise, the dropping temperature is 55°C, the dropping time is 1 hour, and stirring is continued at a speed of 120r / min during the period; S3: after the dropwise addition is completed, the temperature is raised to 70°C and the speed is continuously stirred at 220r / min for 3 hours, and the product solution is centrifuged and vacuum dried to obtain the product.

[0069] The average particle size of silicon dioxide is 25 nm; the average particle size of zinc oxide is 12 nm.

[0070] The preparation process of the modified resin includes the following steps, calculated by mass: S1: adding 4.8 parts of 2-ethylhexyl acrylate, 1.6 parts of isobornyl acrylate and 0.1 part of benzophenone into a reaction container, irradiating the reaction for 2 hours at a wavelength of 360 nm under nitrogen, and filtering the precipitate after the reaction to obtain a prepolymer; S2: uniformly mixing the prepolymer with 32.5 parts of acrylamide, 3.8 parts of malonic acid and 2 parts of hydroxymethyl bisphenol A diglycidyl ether, adding the mixture into 200 parts of acetone solvent, then adding 0.14 parts of benzoyl peroxide, heating to 75°C, stirring the mixture in a closed manner for 6.5 hours, and obtaining a preproduct; S3: mixing 2.4 parts of the preproduct with 1.4 parts of succinic anhydride and 0.22 parts of γ-aminopropyltriethoxysilane in 150 parts of deionized water, maintaining the temperature at 65°C for 2.5 hours, filtering and washing the product after completion, and vacuum drying the mixture to a water content of ≤1wt%.

[0071] The dispersant is dodecyl dimethyl betaine; the structure control agent is paraffin oil #3.

[0072] The vulcanizing agent is DTDM; the accelerator is a combination of MBT and TMTD, and the mass ratio of the two is 2.6:1.2.

[0073] The antioxidant is zinc dibutyl dithiocarbamate; the plasticizer is a composition of dioctyl phthalate and triphenyl phosphate, and the mass ratio of the two is 3.5:0.8.

[0074] The second aspect of the present application provides a preparation process of the above-mentioned high-strength compound rubber, which specifically includes the following steps: S1: adding the base rubber to a mixer, heating to 95°C, and plasticizing for 12 minutes; S2: after plasticizing, adding a mixture of modified nanofiller and dispersant, heating to 118°C, and mixing for 11 minutes; S3: adding a structure control agent and a modified resin, heating to 145°C, and mixing for 8 minutes; S4: continuing to add vulcanizer, accelerator, antioxidant and plasticizer, and cooling to 115°C, mixing for 6 minutes; S5: after completion, cooling to 25°C to obtain a compound, then cutting and granulating the compound, adding it to a vulcanizer, heating to 165°C, vulcanizing for 20 minutes, taking out the product and molding it.

[0075] Comparative Example 1

[0076] The specific implementation of this comparative example is basically the same as that of Example 1, except that the raw materials of the high-strength mixed rubber, in parts by mass, are: 125 parts of base rubber, 17.5 parts of modified nanofiller, 25.6 parts of modified resin, 4.2 parts of dispersant, 2.2 parts of structure control agent, 1.4 parts of vulcanizing agent, 1 part of accelerator, 1.2 parts of antioxidant, and 6.2 parts of plasticizer.

[0077] Comparative Example 2

[0078] The specific implementation of this comparative example is basically the same as that of Example 1, except that the raw materials of the high-strength mixed rubber, in parts by mass, are: 124.5 parts of base rubber, 28.5 parts of modified nanofiller, 12.5 parts of modified resin, 7.8 parts of dispersant, 2.2 parts of structure control agent, 1.4 parts of vulcanizing agent, 1 part of accelerator, 1.2 parts of antioxidant, and 3.4 parts of plasticizer.

[0079] Comparative Example 3

[0080] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation process of the modified nanofiller includes the following steps, calculated by mass: S1: adding 3.8 parts of silicon dioxide to 100 parts of deionized water and stirring evenly, adding 0.58 parts of succinic anhydride and 0.12 parts of γ-aminopropyltriethoxysilane, heating to 65°C, keeping warm and stirring for 3 hours to obtain pretreated silicon dioxide; S2: mixing the pretreated silicon dioxide and 3.6 parts of copper acetate, adding them to 100 parts of DMF solution and stirring evenly, then adding a DMF solution containing 0.75 parts of zinc oxide and 2.2 parts of trimesic acid (a total of 65 parts) dropwise, the dropping temperature is 55°C, the dropping time is 1 hour, and stirring is continued at a speed of 120r / min during the period; S3: after the dropwise addition is completed, the temperature is raised to 70°C and the speed is continuously stirred at 220r / min for 3 hours, and the product solution is centrifuged and vacuum dried to obtain.

[0081] Comparative Example 4

[0082] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation process of the modified nanofiller includes the following steps, calculated by mass: S1: adding 2.65 parts of silicon dioxide to 100 parts of deionized water and stirring evenly, adding 1.55 parts of succinic anhydride and 0.32 parts of γ-aminopropyltriethoxysilane, heating to 65°C, keeping warm and stirring for 3 hours to obtain pretreated silicon dioxide; S2: mixing the pretreated silicon dioxide and 1.6 parts of copper acetate, adding them to 100 parts of DMF solution and stirring evenly, then adding a DMF solution containing 0.22 parts of zinc oxide and 0.8 parts of trimesic acid (a total of 65 parts) dropwise, the dropping temperature is 55°C, the dropping time is 1 hour, and stirring is continued at a speed of 120r / min during the period; S3: after the dropwise addition is completed, the temperature is raised to 70°C and the speed is continuously stirred at 220r / min for 3 hours, and the product solution is centrifuged and vacuum dried to obtain.

[0083] Comparative Example 5

[0084] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of silicon dioxide is 55 nm; the average particle size of zinc oxide is 34 nm.

[0085] Comparative Example 6

[0086] The specific implementation of this comparative example is basically the same as that of Example 1, except that: in parts by mass, the preparation process of the modified resin comprises the following steps: S1: adding 11 parts of 2-ethylhexyl acrylate, 0.2 parts of isobornyl acrylate and 0.1 parts of benzophenone into a reaction vessel, irradiating the reaction vessel with a wavelength of 360 nm under nitrogen for 2 hours, and filtering the precipitate after the reaction to obtain a prepolymer; S2: mixing the prepolymer with 21.5 parts of acrylamide, 1.5 parts of malonic acid and 0.5 parts of The diglycidyl ether of hydroxymethyl bisphenol A is evenly mixed and added to 200 parts of acetone solvent, and then 0.14 parts of benzoyl peroxide is added, and the temperature is raised to 75°C and the reaction is closed and stirred for 6.5 hours to obtain a pre-product; S3: 2.4 parts of the pre-product are mixed with 1.4 parts of succinic anhydride and 0.22 parts of γ-aminopropyltriethoxysilane in 150 parts of deionized water, and the temperature is maintained at 65°C for 2.5 hours. After completion, the product is filtered and washed, and vacuum dried to a water content of ≤1wt%.

[0087] Comparative Example 7

[0088] The specific implementation of this comparative example is basically the same as that of Example 1, except that: in parts by mass, the preparation process of the modified resin comprises the following steps: S1: adding 4.8 parts of 2-ethylhexyl acrylate, 1.6 parts of isobornyl acrylate and 0.1 parts of benzophenone into a reaction container, irradiating the reaction for 2 hours under nitrogen at a wavelength of 360 nm, and filtering the precipitate after the reaction to obtain a prepolymer; S2: mixing the prepolymer with 32.5 parts of acrylamide, 3.8 parts of malonic acid and 2 parts of hydroxyethyl ester; Methyl bisphenol A diglycidyl ether is mixed evenly and added to 200 parts of acetone solvent, followed by adding 0.14 parts of benzoyl peroxide, and the temperature is raised to 75°C and stirred in a closed manner for reaction for 6.5 hours to obtain a pre-product; S3: 5.5 parts of the pre-product are mixed with 0.8 parts of succinic anhydride and 0.11 parts of γ-aminopropyltriethoxysilane in 150 parts of deionized water, and the temperature is maintained at 65°C for reaction for 2.5 hours. After completion, the product is filtered, washed, and vacuum dried to a water content of ≤1wt%.

[0089] Performance Evaluation

[0090] Mechanical properties: Mechanical properties of the rubber mixtures prepared in the examples and comparative examples were tested. The tensile strength and tear strength of the rubber mixtures were measured according to GB / T528 and GB / T 529 standards, respectively. The average values ​​of 10 tests were recorded in Table 1.

[0091] Waterproof property: The rubber mixtures prepared in the examples and comparative examples were tested for their water vapor permeability according to GB / T 16578.3 standard. The test values ​​were averaged over 10 tests and recorded in Table 1.

[0092] Aging resistance: The mixed rubber obtained in the embodiments and comparative examples was prepared into 5cm×5cm×1cm samples, which were placed in a constant temperature and humidity chamber at 65°C and 75% relative humidity for 6 months. After 6 months, it was observed whether there was yellowing, oxidation, blistering or breakage. If so, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group, and the qualified rate of the test was recorded in Table 1.

[0093] Table 1 Performance test results

[0094]

[0095] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of mechanical properties, waterproof properties and aging resistance. This is mainly due to the result of the combined effect of the modified resin and modified nanofiller specified in the present application. After the modified nanofiller is added, the active connection with the rubber molecules is carried out through the connection effect of the filler surface groups, and the connection strength of the rubber system is greatly enhanced through the intermolecular force therebetween, thereby improving the mechanical strength. In addition, the framework structure in the modified nanofiller can be used to absorb internal moisture and construct a hydrophobic surface, thereby obtaining good waterproof and mechanical properties. On the other hand, the addition of the modified resin can produce a good cross-linking effect with the rubber system through the multi-active groups it carries, greatly increasing the compactness of the internal network structure of the rubber system, thereby greatly limiting the migration efficiency of free groups, free water molecules and active molecules in the rubber system after molding, and can also become a mobile dispersion carrier for the modified nanofiller, thereby increasing the penetration resistance of water molecules to the system. Among the comparative examples, because the modified nanofillers and modified resins in the correct proportions were not used in comparative examples 1 and 2, their effects in the compounded rubber were reduced, thereby reducing the overall performance. In comparative examples 3 to 7, the different preparation methods of the modified nanofillers and modified resins directly affected the particle composite structure morphology and the resin molecular chain system of the modified nanofillers, thereby greatly affecting their joint effects in the compounded rubber system, and further affecting their various performances.

Claims

1. A high-strength mixed rubber, characterized in that: The raw materials are as follows: 80-120 parts of base rubber, 25-45 parts of modified nanofiller, 20-30 parts of modified resin, 5-10 parts of dispersant, 2-4 parts of structure control agent, 1-2 parts of vulcanizing agent, 0.5-1.5 parts of accelerator, 1-2 parts of antioxidant, and 4-10 parts of plasticizer. The mass ratio of the base rubber, modified nanofiller and dispersant is (9-11): (2.8-4): (0.6-0.8); The mass ratio of the base rubber, modified resin and plasticizer is (9-11): (2.2-2.8): (0.5-0.8); The base rubber is a composition of methyl vinyl silicone rubber and nitrile rubber; The mass ratio of the methyl vinyl silicone rubber to the nitrile rubber is (3-4): (1.5-2); The vinyl content of the methyl vinyl silicone rubber is 3-4.5%; Preparation process of the modified nanofiller The following steps are involved: S1: Add deionized water to silica and stir evenly, add succinic anhydride and γ-aminopropyltriethoxysilane, heat to 65-70°C, stir and react for 2-3 hours to obtain pretreated silica; S2: Add the pretreated silica and copper acetate to the DMF solution and stir evenly, then drop the DMF solution containing zinc oxide and trimesic acid, the dropping temperature is 50-55°C, the dropping time is 1-1.5h, and the stirring is continued at 100-140r / min; S3: After the dropping is completed, the temperature is raised to 70-75°C and the stirring is continued at 200-240r / min for 3-4h. After completion, the product solution is centrifuged and filtered, and vacuum dried to obtain; The mass ratio of the silicon dioxide, succinic anhydride and γ-aminopropyltriethoxysilane is (2.5-2.8): (1.5-1.6): (0.3-0.35); The mass ratio of silicon dioxide, zinc oxide, copper acetate and trimesic acid is (2.5-2.8): (0.5-0.8): (3-4): (2-2.5); The average particle size of the silicon dioxide is 25-30 nm; The average particle size of the zinc oxide is 10-15 nm; The preparation process of the modified resin comprises the following steps: S1: adding 2-ethylhexyl acrylate, isobornyl acrylate and benzophenone into a reaction container, irradiating the reaction under nitrogen at a wavelength of 300-380nm for 1-2h, filtering the precipitate after the reaction is completed, and obtaining a prepolymer; S2: uniformly mixing the prepolymer with acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether, adding the mixture into an acetone solvent, then adding benzoyl peroxide, heating the mixture to 70-80°C, stirring the mixture in a sealed manner for 5-7h, and obtaining a preproduct; S3: mixing the preproduct with succinic anhydride and a silane coupling agent in deionized water, maintaining the temperature at 65-70°C for reaction for 2.5-3h, filtering and washing the product after completion, and vacuum drying the product until the water content is less than or equal to 1wt%.

2. The high-strength compound rubber according to claim 1, characterized in that: The weight average molecular weight of the methyl vinyl silicone rubber is 500,000 to 700,000.

3. The high-strength compound rubber according to claim 2, characterized in that: The mass ratio of 2-ethylhexyl acrylate, isobornyl acrylate, acrylamide, malonic acid and hydroxymethyl bisphenol A diglycidyl ether is (4-6): (1-2): (30-35): (3-5): (1.5-2).

4. The high-strength compounded rubber according to claim 3, characterized in that: The dispersant is at least one of lauryl alcohol polyoxyethylene ether, cetyl stearyl alcohol polyoxyethylene ether, dodecyl dimethyl betaine, and sodium dodecylbenzene sulfonate.

5. The high-strength compounded rubber according to claim 4, characterized in that: The structure control agent is at least one of paraffin oil, naphthenic oil, vegetable oil and polyethylene wax.

6. The high-strength compounded rubber according to claim 5, characterized in that: The vulcanizing agent is at least one of DTDM, DPTU, DCP and sulfur powder; the accelerator is at least one of MBT, MBTS, CBS, TBBS, TMTD, ZBEC, ZDEC and ZDBC.

7. A process for preparing the high-strength mixed rubber according to any one of claims 1 to 6, characterized in that: The specific steps include: S1: Add the base rubber to the mixer, heat it to 90~100℃, and plasticize for 10~15min; S2: After plasticizing, add the mixture of modified nano filler and dispersant, heat it to 110~120℃, and mix it for 10~15min; S3: Add the structure control agent and modified resin, heat it to 140~150℃, and mix it for 5~10min; S4: Continue to add vulcanizer, accelerator, antioxidant and plasticizer, and cool it to 110~120℃, and mix it for 5~10min; S5: After completion, cool it to 20~30℃ to obtain the mixture, then cut the mixture into granules, add it to the vulcanizer, heat it to 160~180℃, vulcanize it for 15~25min, take out the product and shape it.

Citation Information

Patent Citations

  • Heavy-load high-elasticity rubber and preparation method thereof

    CN115449135A

  • Sealing rubber strip and preparation method thereof

    CN116285125A